The influence of product quality, brand image, and electronic-word of mouth on purchasing decisions (study on consumers of Bandeng Presto Bucin) - Sukma Putri Pertiwi; Kristina Anindita Hayuningtias (SEAN Institute, 2024)
Sales of milkfish presto bucin experience a fluctuating cycle every month. In order to find out the cause, this study is intended to determine the influence of product quality, brand image, and electronic-word of mouth on purchasing decisions at Bandeng Presto Bucin. The research conducted on Presto Bucin milkfish consumers took samples with purposive sampling techniques, which are sampling techniques by selecting samples according to predetermined criteria. The data analysis used is multiple linear regression. From the processing of research data, it is proven that product quality, brand image, and electronic-word of mouth affect the purchase decision of Bandeng Presto Bucin.